Ultrasonographic evaluation of fetal sacral length and correlation with gestational age. - Syed Abdul Quader; Md Saiful Islam; Md Menhazul Islam; Md Zakir Hossain (Update Dental College, 2016)
Background: During the last three decades, ultrasonographics of a number of fetal osseous structures have been adopted for the assessment of gestational age and the evaluation of fetal growth and development. The most frequently used morphometric parameters include biparietal diameter, head circumference and femur length. Moreover, nomograms for other osseous structures, such as mandible, clavicle, scapula, vertebral arch, iliac bone and foot length have been established. Another suggestion is to measure the length of fetal sacrum, which should be visualized as a part of routine ultrasonographic evaluation of a fetus. Hence, associated congenital anomalies such as sacral agenesis or sacrococcygeal teratoma can be detected simultaneously Objective: To evaluate the usefulness of fetal sacral length in determination of gestational age at 15th to 40th weeks of pregnancy. Method: This study was carried out on 441 normal pregnant women between 15 to 40 weeks of gestation over a period of 24 months to find out the correlation between gestational ages with fetal sacral length measured by ultrasonographically. 41 patients were excluded from my study as 09 had multiple pregnancies, 02 had fetal congenital anomaly; out of them one had anencephaly and one had lumbo-sacral meningocele and complete visualization of sacrum was not possible for 30 fetuses. Result: Measurements of fetal sacral length were performed by utilizing gray scale real time ultrasound scanner equipped with 3.5 MHz convex transducer and gestational age was estimated by LMP.The mean gestational age was 27.52 with standard deviation of mean (±SD) was ± 7.28 weeks and gestational age ranging from 15 to 40 weeks. 40.0% percent were Primigravida, 31.75% percent were 2ndgravida, 18.25 percent were 3rdgravida, 7.75 percent were 4th gravid and 1.75% percent were 5th and more gravida. Most of the cases were Primigravida and 2ndgravida. A positive significant correlation were found between fetal sacral length with gestational age (wk) (r=0.998; p<0.001 and R²=99%) Conclusion:In this study it is observed that there is significant correlation of fetal sacral length with estimated fetal age so, it can be concluded in the present study that fetal sacral length(FSL) can be used as a parameter for estimation of gestational age. Update Dent. Coll. j: 2016; 6 (1): 08-14